Analisis Laporan Realisasi Anggaran Untuk Mengukur Kinerja Keuangan Dinas Tenaga Kerja Sumatera Utara - Putri Ramadana; Alsanah Alsanah; Desi Arianta Br Surbakti; Fachri Ikram; Yulia Sari Purba (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze budget realization reports in measuring the financial performance of the Manpower Agency of North Sumatra Province for the period 2018-2022. The descriptive quantitative method was used by analyzing secondary data in the form of budget realization reports obtained from the official website of the North Sumatra provincial government. The results showed that the average effectiveness ratio was 80.49% which was included in the quite effective criteria, while the average efficiency ratio was 25.43% which was included in the very efficient criteria. In general, it can be concluded that the financial performance of the manpower agency was quite good but still needs improvement to achieve the targets that have been set.